2005
DOI: 10.1108/02686900510625325
|View full text |Cite
|
Sign up to set email alerts
|

ABC: adopters, supporters, deniers and unawares

Abstract: PurposeDespite the great interest in activity based costing (ABC), companies seem to be reluctant to adopt it. Our research aims at examining the rate of adoption of ABC by Greek companies that belong to all three sectors of the Greek economy, i.e. manufacturing, retail and services, as well as investigating the reasons that influence a firm's decision to change its current cost accounting system.Design/methodology/approachAn empirical survey via questionnaires was conducted during 2003 on a sample of 88 Greek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 19 publications
8
100
0
15
Order By: Relevance
“…Using the Cramer's V, the link may be considered strong (V Cramer=0.405;). These results are consistent with the findings of Cohen et al (2005), and Machado (2012Machado ( , 2013, which state that the older officers do not know the more advanced methods of management accounting.…”
Section: Figure 1 -Knowledge Of the Approach By Activities And Gendersupporting
confidence: 89%
See 3 more Smart Citations
“…Using the Cramer's V, the link may be considered strong (V Cramer=0.405;). These results are consistent with the findings of Cohen et al (2005), and Machado (2012Machado ( , 2013, which state that the older officers do not know the more advanced methods of management accounting.…”
Section: Figure 1 -Knowledge Of the Approach By Activities And Gendersupporting
confidence: 89%
“…Regarding the second group of variables responsible for disseminating the management accounting methods, several authors (Clarke et al, 1999;Cohen et al, 2005;Machado 2012Machado , 2013 have analyzed some financial officers' characteristics such as the educational background, gender and age. Clarke et al, (1999) concluded that the officers' poor educational background is one of the main inhibitors to change in the methods used by the Irish companies.…”
Section: -Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Advocates tend to describe ABC as an improved approach for the allocation of overhead costs, the management of operating costs, or as a managerial technology for the costing and monitoring of activities which involves tracing resource consumption and costing final outputs (Baird et al 2004;Cohen et al 2005;Gosselin 2007). Contemporaneously, they suggest that the use of ABC changes-and potentially illuminates-the processes of cost estimation, the level of detail of cost input to the budgeting process, and the obtainable variance feedback (e.g., Drake and Haka 2008).…”
Section: Introductionmentioning
confidence: 99%